2015
DOI: 10.7763/ijesd.2015.v6.552
|View full text |Cite
|
Sign up to set email alerts
|

Substance Flow Analysis of Phosphorous in China

Abstract: Phosphorous is an essential natural resource that is projected to run out rapidly. Environmental pollution and resource scarcity pressures require the development of a phosphorous management system in China. One of the fundamental steps to achieve this is to understand the way that phosphorous flows throughout the country. It helps to find out the current phosphorous utilization conditions and provide reliable evidence for both technology and strategy development. Based on these reasons, substance flow analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…PUE of the livestock sector in China was only 7% [4]. One important reason for this low PUE is that since modern market-oriented farming gradually replaced traditional self-efficient farming, the increasing need for pork and use of animal feed promoted the development of intensive farming, particularly around large cities such as Beijing, Shanghai and Guangzhou.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PUE of the livestock sector in China was only 7% [4]. One important reason for this low PUE is that since modern market-oriented farming gradually replaced traditional self-efficient farming, the increasing need for pork and use of animal feed promoted the development of intensive farming, particularly around large cities such as Beijing, Shanghai and Guangzhou.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, various studies have focused on identifying low PUE sectors, controlling of P losses, or recoveries [3]. It has been reported that the global livestock sector is considered one of the main contributors to serious global environmental problems [4]. PUE of the livestock sector is low [5], and causes a high risk of losing P to the environment.…”
Section: Introductionmentioning
confidence: 99%